2018
DOI: 10.5194/acp-18-921-2018
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol characteristics and particle production in the upper troposphere over the Amazon Basin

Abstract: Abstract. Airborne observations over the Amazon Basin showed high aerosol particle concentrations in the upper troposphere (UT) between 8 and 15 km altitude, with number densities (normalized to standard temperature and pressure) often exceeding those in the planetary boundary layer (PBL) by 1 or 2 orders of magnitude. The measurements were made during the German-Brazilian cooperative aircraft campaign ACRIDICON-CHUVA, where ACRIDICON stands for "Aerosol, Cloud, Precipitation, and Radiation Interactions and Dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
182
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(255 citation statements)
references
References 189 publications
(265 reference statements)
37
182
0
7
Order By: Relevance
“…These climatological streamlines are derived from a reanalysis of the period from 1981 to 2010. As shown in Andreae et al (), similar wind patterns were found during the AC campaign in September 2014. LT winds over the Amazon Basin are strongly influenced by the Andes mountain range (Campetella & Vera, ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These climatological streamlines are derived from a reanalysis of the period from 1981 to 2010. As shown in Andreae et al (), similar wind patterns were found during the AC campaign in September 2014. LT winds over the Amazon Basin are strongly influenced by the Andes mountain range (Campetella & Vera, ).…”
Section: Resultssupporting
confidence: 83%
“…Pyroconvection therefore likely has a negligible direct effect on UT CO concentrations. In contrast, observations over Amazonia indicate a strong link between deep convection and UT CO (Andreae, et al, , ). For example, the influence of deep convection on UT CO over the southern Amazon Basin at the end of the dry season is illustrated by the nearly simultaneous sharp rise in CO and ice water content products derived from Microwave Limb Sounder satellite observations at 215 hPa (Livesey et al, ).…”
Section: Resultsmentioning
confidence: 96%
“…Weigelt et al (2009) measured upper-troposphere particle number size distributions over different regions around the world, and found a frequent presence of nucleation mode particles whenever the measured air masses had been in recent contact with deep convective cloud systems. Similar observations had already been reported over the Indian and Pacific Oceans (de Reus et al 2001, Clarke and Kapustin 2002), and over the Amazon Basin (Andreae et al 2018). Theoretical analysis and model simulations support the view that clouds associated with deep convection provide favorable conditions for NPF, however the precursors, nucleation mechanisms and exact location of NPF with respect to clouds remain to be quantified (Kulmala et al 2006b, Ekman et al 2008, Waddicor et al 2012.…”
Section: Cloud-induced Npfsupporting
confidence: 71%
“…Biomass burning is one of the largest sources of aerosol particles and many trace gases in the global atmosphere (Andreae andMerlet 2001, Van Marle et al 2017). Laboratory experiments conducted by Hennigan et al (2012) demonstrated that biomass burning plumes have a great potential for NPF and subsequent particle growth, yet there are very few field studies on this phenomenon.…”
Section: Ft and Mountain Sitesmentioning
confidence: 99%
“…For example, English et al (2011) evaluated a range of nucleation mechanisms in the stratosphere against Stratospheric Aerosol and Gas Experiment II SAGE II data. Future modeling studies will need to include the contribution of organic compounds to NPF in the free troposphere, following observations over the Amazon (Andreae et al, 2018) and cloud-resolving model simulations (Ekman et al, 2008;Murphy et al, 2015).…”
Section: Modeling Npf In the Boundary Layer And Free Tropospherementioning
confidence: 99%